Central Corneal Thickness in Fuchs’ Uveitis Syndrome - Pınar Çakar Özdal; Alper Yazıcı; Ufuk Elgin (Türk Oftalmoloji Dergisi)
Purpose: To investigate whether the central corneal thickness (CCT) values of uveitic eyes were different from those of nonuveitic eyes and of control subjects and whether the intraocular pressure (IOP) was associated with the CCT in patients with Fuchs’ uveitis syndrome (FUS). Material and Method: Fifty-one unilaterally involved FUS patients and 51 age- and gender-matched control subjects were included in the study. Complete ophthalmologic examinations and pachymetry measurements were performed. CCT and IOP values were compared between involved, uninvolved and control group eyes. Results: The groups were age- and gender-matched. No significant difference was found between the mean CCT values of the involved (561.1±43.7 µm) and uninvolved (564.6±45.7 µm) eyes (p= 0.08). When compared with the control group (547.7±36.9 µm), only uninvolved eyes CCT was found to have significant difference (p=0.04). The mean IOP was 14.4±7.2 mmHg and 14.6±3.4 mmHg in involved and uninvolved eyes of FUS patients, respectively. Elevated IOP or glaucoma was present in 13/51(25.5%) patients in the FUS group. The mean IOP (12.9±2.4 mmHg) in the control group did not reveal any significant difference compared to FUS group. Discussion: The chronic low-dose inflammation does not affect corneal thickness as much as an acute inflammation, and the IOP might be associated with CCT in FUS. (Turk J Ophthalmol 2013; 43: 225-8)